A Preliminary Attempt To Reduce Total Dissolved Solids In Ground Water Using Different Plant Parts - ANEEZ EBRAHIM; MOHAMMED ALI; GAUTHAM; N.JAWAHAR; SEKARBABU HARIRAM (International Journal of Pharma and Bio Sciences, 2011)
The present study is a preliminary attempt to explore plant materials such as Indian gooseberry bark (Phyllanthus emblica), lemon peel (Citrus limon), peanut husk (Arachis hypogaea) and vetiver root (Vetiveria zizanoides) for reducing the total dissolved solids (TDS) in a domestic ground (hard) water. The water samples were collected from bore well in the out skirts of Chennai to screen the TDS ,which was around1400ppm (parts per million) using a TDS meter. The selected plant materials were packed in vertical glass columns separately and 50mL of hard water is supplied to the column to switch on the process with the flow rate of 10 ml per minute. The reduction of dissolved solids content in the samples were screened .The %decrease of TDS in the elute water samples are calculated for both first loading and second loading. It is evident that vetiver root has shown a maximum reduction in TDS (55.93%) followed by gooseberry bark (42.14%) , lemon peel (42%) and peanut husk (41.14%).